2011
DOI: 10.1016/j.jcm.2011.01.008
|View full text |Cite
|
Sign up to set email alerts
|

A case of pseudo–angina pectoris from a pectoralis minor trigger point caused by cross-country skiing

Abstract: This case demonstrates the importance of differential diagnosis and mechanism of injury in regard to chest pain and that chiropractic management can be successful when addressing patients with chest wall pain of musculoskeletal origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…A grade 1 strain on imaging is defined as having edema without laxity in any fibers or gapping within the myotendinous complex. Pectoralis minor grade 1 strains have been confused in the past with symptoms of angina [9]. Grade 2 stains demonstrate laxity in fibers indicating significant strain but without tissue gapping.…”
Section: Discussionmentioning
confidence: 99%
“…A grade 1 strain on imaging is defined as having edema without laxity in any fibers or gapping within the myotendinous complex. Pectoralis minor grade 1 strains have been confused in the past with symptoms of angina [9]. Grade 2 stains demonstrate laxity in fibers indicating significant strain but without tissue gapping.…”
Section: Discussionmentioning
confidence: 99%
“…47 An increase in instrument angle results in deeper penetration as well as heavier pressure promoted healing to a greater degree. 10,47 Previous studies have found that GT can reduce anterior chest pain due to a pectoralis minor trigger point, 49 improve carpal tunnel syndrome, 14 increase posterior shoulder range of motion, 12,13 and decrease the amount of fibrotic adhesions and hypertonicity which increased range of motion, decreased pain and increased functionality in a post-operative ACL rupture. 50 GT has also been shown to be beneficial in other soft tissue restrictions and adhesions, tendinitis, musculoskeletal ailments and ROM restrictions.…”
Section: Instrument Assisted Soft Tissue Mobilizationmentioning
confidence: 99%
“…These pathologies are the potential mechanisms of underlying pain in PM muscle and neurovascular compression. [4,[10][11][12] Repetitive sports or daily activity can also cause vascular PMS. [3][4][5] The PM muscle, itself, can compress some of the vessels, or the head of the humerus exert pressure on the vascular structures during throwing and forceful overhead movements of the upper extremity.…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…There is a broad spectrum of clinical presentation with pain in the arm, shoulder, neck, chest, and scapular region, and weakness, paresthesia, swelling and coldness in the upper extremity. [1,2,10,12] Another important issue is the age range of patients. Pectoralis minor syndrome can be seen in all ages and sexes.…”
Section: Clinical Presentationmentioning
confidence: 99%